VALUASI EKONOMI DAMPAK PERPINDAHAN KAMPUS UNDIP PLEBURAN DI TEMBALANG DAN STRATEGI PENGEMBANGAN WILAYAH DI KECAMATAN TEMBALANG - Suryanto D Sipahutar; Indah Susilowati (Diponegoro Journal of Economics, 2012)
ABSTRACT The Undip’s campus movement from Undip Pleburan to Tembalang in academic year 2010/2011 has made positive and negative impact for the region and community in Tembalang. The impact of that campus movement involve socio-cultural, economy, and environment aspect. This study intend to (1) identify the impact in socio-cultural, economy, and environment aspect due to Undip’s campus movement from undip Pleburan to Tembalang; (2) estimate positive and negative impact in socio-cultural, economy, and environment aspect that due to Undip’s campus movement from undip Pleburan to Tembalang; (3) build the development strategy for region around the Undip’s Tembalang campus. This study used primary and secondary data. The primary data of this study got from 41 respondents as sample used purposive sampling method. The secondary data got from academic administration office of Diponegoro university. To achieve the first and second purpose this study used economic valuation method namely B/C analysis and risk assessment. Analysis Hierarchy Proccess used to achieve the third purpose. The Undip’s campus movement from Undip Pleburan to Tembalang is a feasible project. It is based on benefit and cost analysis where benefit/cost is 8.43 means >1. However, development strategies is still be required to make the region around the Undip’s Tembalang campus better. There are three aspect that considered to build the development strategy namely socio-cultural, economy, and environment aspect. Based on analysis, the first priority in build development strategy is (1) repair damage roads (value 0.126); (2) new shops licensing arrangements (value 0.10); (3) build the alternative pathway (value 0.90). The results showed that special attention to solve negative impact in socio-cultural and environment impact especially for criminality and congestion. The ways to do are repair damage roads, new shops licensing arrangements, build the alternative pathway, and community assembly.